EVALUASI PROGRAM BINCANG BISNIS MAHASISWA PADA HIPMI PERGURUAN TINGGI KALIMANTAN BARAT DI PONTIANAK - Apriliyanto, Sutrisno; Achmadi, Achmadi; Buwono, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This study aimed to determine the evaluation of student business talk programs at the HIPMI universities of west Kalimantan in Pontianak. The method used is a qualitative method with the aim of describing the actual picture of the phenomena that occur in the object under study. In this study, the object was a student business talk program by the HIPMI universities of west Kalimantan.. The respondents of this study were administrators and members of the HIPMI universities of west Kalimantan. Data retrieval using instruments in the form of interviews and data from the HIPMI universities of west Kalimantan that supports. Based on the results of the study it can be concluded that the student business talk program at the HIPMI o universities of west Kalimantan in Pontianak is included in the less effective category. For this reason, it is suggested: (1) the program objectives are conveyed to program participants in depth, so that there are targets to develop their business or create business opportunities for participants who are just starting, (2) The program implementation schedule should be neatly arranged, so there is no decrease, (3) The implementation of the student business talk program at the HIPMI o universities of west Kalimantan  should be conducted in stages by the management, in addition to improving the quality of the program, it can also overcome internal management problems, (4) Providing mentors to participants in student business talk programs so that there are always developments in improving entrepreneurial spirit. Keywords : HIPMI Universities, Program Evaluation